2022
DOI: 10.3389/fpubh.2022.878703
|View full text |Cite
|
Sign up to set email alerts
|

How to Improve Cancer Prevention Knowledge? A Way to Identify Gaps and Tackle the Limited Availability of Health Education Services in Primary Health Care Using the European Code Against Cancer

Abstract: IntroductionThe first line of action against cancer is primary and secondary prevention. Increased efforts are needed in countries where cancer mortality is high and the healthcare system is inefficient. Objectives: Our aim was to present a new solution to identify and fill gaps in health education services in accordance with the European Code Against Cancer (ECAC).Materials and MethodsThis study was carried out in a rural population of 122 beneficiaries of health education workshops financed by the Polish Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…In line with previous studies ( 5 , 9 , 11 ), we also found that residents in urban areas or with a family history of cancer were more likely to have a higher core knowledge rate. The differences seen when comparing areas of residence can be explained by the urban-rural disparity in access to health services and exposure to certain risk factors ( 20 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In line with previous studies ( 5 , 9 , 11 ), we also found that residents in urban areas or with a family history of cancer were more likely to have a higher core knowledge rate. The differences seen when comparing areas of residence can be explained by the urban-rural disparity in access to health services and exposure to certain risk factors ( 20 ).…”
Section: Discussionsupporting
confidence: 93%
“…Currently in China, urban-rural disparities are obvious, with people living in urban areas having greater cancer knowledge as well as higher cancer rates ( 21 ). In addition, a family history of cancer may reflect genetic as well as behavioral and environmental risks shared by family members ( 9 ). Health promotion theories, such as the Health Belief Model and protection motivation, predict that people are more likely to take preventive actions when they perceive their risk of negative health outcomes to be high ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to determine the level of knowledge about cancer in university students studying in the field of health and to increase their lacking knowledge. 7 Previous studies revealed the lack of knowledge of university students about cancer topics. [8][9][10][11] Irfan et al showed that pharmacy and physiotherapy students did not have knowledge regarding the procedures of breast self-examination in Pakistan.…”
Section: Introductionmentioning
confidence: 99%